The Form and Function of The Context in The Conversations Language and Literature Education Study Program Students Using Pragmatic Studies - Nustelu, Efline; Sasabone, Carolina (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The purpose of this research is to find out the context form and function of context in the conversations of Indonesian language and literature education study program students using pragmatic studies. This research is a type of qualitative research in which this research uses more word to deswcribe the form context and function of the context in the conversations of Indonesian language and literature education study program students. The data collection techniques used in this study were observation techniques, field note techniques. The results of this study indicate that the form context and function of the context in the conversations of indesian language and literature education study has 4 context functions, namely the function of providing information.